RETHINKING ISLAMIC BRANDING: IS A NEW PHILOSOPHICAL ASSUMPTION NECESSARY? - Muhammad Saiful Islam Ismail; Syaimak Ismail; Aemy Aziz; Ahmad Afiq Irshad Omar; Muhammad Saiful Islami Mohd Taher; Suheil Che Sobry; Muhammad Khairul Zharif Nor A'zam, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The American Marketing Association (AMA) defines a brand as “a name, term, design, symbol, or any other feature that distinguishes one seller's goods or services from those of others”. Ideally, a brand provides consumers with multiple sensory cues that enhance their connection to a company's product. It is also involves forming a perception in consumers' minds and hearts. In 2007, Islamic branding began to capture the attention of marketing scholars. Discussions on Islamic branding can be categorized into three main areas: defining what constitutes an Islamic brand, proposing models or frameworks for Islamic branding, and examining the factors that influence Muslim consumers' attitudes toward a brand. It can be observed that most Islamic branding studies are rooted in conventional frameworks, which may not fully align with Islamic philosophy. This raises questions about whether the current philosophical assumptions underlying Islamic brand studies comply with Islamic principles? Consequently, this study seeks to explore the philosophy of Islamic branding from an Islamic perspective, contrasting it with secular approaches. The scope of this article encompasses the epistemology, ontology, and axiology of brand studies. This article utilizes a qualitative approach through library research, conducting an in-depth examination of existing literature related to both secularism and Islamic philosophy. Finding indicated Islamic brands may exhibit unique characteristics, values, and distinctiveness grounded in the fundamental sources of the Quran and Sunnah. Hence, the present article recommend that the development of Islamic brand must following the epistemology, ontology, and axiology from Islamic philosophy perspective. This philosophy should be as a reference to the marketers as well as Islamic marketing scholars in creating the true Islamic brand product in order to achieve His Blessings in the world and Hereafter.